Spectrophotometric Determination of Trace Zinc in Yeast by Using 2-(5-Bromo-2-pyridylazo)-5-diethylaminophenol - Cheng1, Xianzhong; Peng1, Yuan; Shu2, Jing; Zhang1, Shunxi; Zhou1, Guoqing (Asian Journal of Chemistry, 2013)
A simple and rapid spectrophotometric method is described for the determination of trace zinc(II) in zinc-enriched yeast using 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP) as a chromogenic reagent in the presence of surfactant OP. The analytical parameters such pH, reagent and coexistent ions were investigated. The results showed that the maximum absorption wavelength of the complex Zn-5-Br-PADAP was identified at 556 nm. The apparent molar absorptivity was 1.16 × 105 L mol-1 cm-1. Beer’s law was obeyed in the concentration range of 0~12 μg/25 mL for zinc. The interference of various ions was studied by sodium citrate and thiourea as masking agents. The proposed method has been applied to the determination of Zn in yeast-enriched samples with satisfactory and results agreed with those provided by atomic absorption spectrometry.